Cross trading by investment advisers: Implications for mutual fund performance - Casavecchia, Lorenzo; Tiwari, Ashish (Journal of Financial Intermediation, 2016)
Using a unique dataset we provide new evidence on the significant penalty on client fund performance due to conflicts of interest related to the cross trading (TCT) activities of mutual fund advisers: funds managed by advisers in the top TCT quintile significantly underperform funds managed by advisers in the bottom TCT quintile by 1% per year. Adviser incentives to engage in cross trading are directly related to their opportunities for generating revenues from affiliated trading operations. Additional tests suggest that the significantly higher trading commissions paid by client funds of high-TCT advisers are a major source of their under-performance.